Interlibrary loan services in academic libraries: a case study on its effectiveness in Perpustakaan Tun Abdul Razak 1, Shah Alam / Noraishah Abdullah - Abdullah, Noraishah (2003)
Interlibrary loan services have provided the means of sharing resources and thereby meeting user needs especially in academic libraries. · This study examines the perception of students towards interlibrary loan services in PTAR 1. It attempts to find out how students feel towards these services regarding the usage, staff assistance, actual needs and expectations. The questionnaire was used as a method of gathering information. 50 respondents in PTAR 1 were chosen randomly in this study. The Statistical Package of Social Science (SPSS) version 11.5 was used to analyze the data. The study has identified that the lack of knowledge and awareness of the service makes the ILL ineffective to users. Suggestions and recommendations are made based on the findings to improve the services in the future. The study concludes that the ILL services are very important and useful to the students.